Legal Protection Of Children From Victims Of Criminal Acts With The Mode Of Romantic Relationship By Adults - Tiara Rebecca Kezia Siregar; Beniharmoni Harefa (PALAR | PAKUAN LAW REVIEW, 2026)
This study examines the legal protection for children as victims of criminal acts involving the "romantic relationship" modus operandi (child grooming) by adults. This phenomenon frequently blurs the line between consensual relationships and sexual exploitation due to psychological manipulation and power imbalances. The central problems addressed in this research are the qualification of manipulative actions within romantic relationships as criminal offenses and the synchronization of norms between Law Number 35 of 2014 and Law Number 1 of 2023 to ensure legal certainty for victims. The research utilizes a normative juridical method with a statutory and conceptual approach. The findings indicate that a child's consent in such relationships is vitiated consent (apparent consent) due to disparities in age, maturity, and bargaining power. Furthermore, Law 1/2023 (the New Criminal Code), through Articles 415 and 417, accommodates this modus operandi in greater detail by including the abuse of authority, the provision of rewards, and deception. This represents an evolution in regulation compared to the Child Protection Law, which remains general in its formulation of the element of deceit. Consequently, harmonization of these regulations is necessary to strengthen comprehensive legal protection for children. Keywords: Child Protection, Romantic Relationships, Child Grooming, New Criminal Code (KUHP), Psychological Manipulation.